2013
DOI: 10.1016/j.jtbi.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Exact results for amplitude spectra of fitness landscapes

Abstract: Starting from fitness correlation functions, we calculate exact expressions for the amplitude spectra of fitness landscapes as defined by Stadler [1996. Landscapes and their correlation functions. J. Math. Chem. 20, 1] for common landscape models, including Kauffman's NK-model, rough Mount Fuji landscapes and general linear superpositions of such landscapes. We further show that correlations decaying exponentially with the Hamming distance yield exponentially decaying spectra similar to those reported recently… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(87 citation statements)
references
References 51 publications
2
85
0
Order By: Relevance
“…One demonstrates several intriguing regularities among higher-order interactions in a meta-analysis of 113 combinatorially complete experiments from the engineering literature [46]. The other shares our specific interests in the statistical properties of fitness landscapes [47]. …”
Section: Conclusion: Evolutionary Biologists Should Worry About Highmentioning
confidence: 99%
“…One demonstrates several intriguing regularities among higher-order interactions in a meta-analysis of 113 combinatorially complete experiments from the engineering literature [46]. The other shares our specific interests in the statistical properties of fitness landscapes [47]. …”
Section: Conclusion: Evolutionary Biologists Should Worry About Highmentioning
confidence: 99%
“…We decomposed the fitness landscape into epistatic interactions of different orders by Fourier analysis (Stadler, 1996;Szendro et al, 2013;Weinreich et al, 2013;Neidhart et al, 2013). The Fourier coefficients given by the transform can be interpreted as epistasis of different orders (Weinreich et al, 2013;de Visser and Krug, 2014).…”
Section: Fourier Analysismentioning
confidence: 99%
“…Franke et al (2011) applied the model to an eight-locus fitness landscape for the fungus A. niger and extracted an estimate of c from a subgraph analysis of pathway accessibility. In a study of amplitude spectra of fitness landscapes Neidhart et al (2013) showed that the correlation function of a six-locus fitness landscape obtained by Hall et al (2010) for the yeast Saccharomyces cerevisiae is well described by the RMF model. Finally, in a metaanalysis of 10 empirical fitness landscapes Szendro et al (2013b) used the RMF model to interpolate the behavior of various ruggedness measures between the limits of a completely random (HoC) and an additive landscape and found good agreement with the trends in the empirical data.…”
Section: Application To Experimentsmentioning
confidence: 99%